Agent-Based Simulation Disaster Evacuation Awareness on Night Situation in Aceh - Sinung Widiyanto; Dimas Adi; Rahul Vijay Soans (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
In 2004 at least 230,000 people were victims of the Aceh tsunami disaster. To prevent the recurrence of many victims, the Aceh government held an evacuation exercise in 2008. To improve effectiveness dan reduce the cost reduction during evacuations drills, simulation is the best option. Agent-Based Modeling is a simulation program that was employed for tsunami evacuation in Aceh. This study on tsunami evacuation using agent-based modelling presented and evaluated the different control parameters that affect the evacuation rate. Evacuation scenario during day or night has different environmental, agent base, road modelling, and population approach. The Road Network Model has explained that to analyze the effect of agents in the evacuation process, resident agents are presumed to know the direction and shortest path to the nearest evacuation points. This simulation designed in Netlogo is also able to assess the congestion possibility on the road network. The road network emphasized the different scenarios to discover the possibility of congestion points. Nighttime is proven to be the best scenario for performing the evacuation in the simulation. The key reason to select the night scenario is to maximize the effects of an evaluation of the road network. In addition, simulation using night scenarios is also expected to raise people’s awareness.